Cytotoxicity of Medicinal Plant Species Used by Traditional Healers in Treating People Suffering From HIV/AIDS in Uganda - Anywar, Godwin Upoki; Kakudidi, Esezah; Oryem-Origa, Hannington; Schubert, Andreas; Jassoy, Christian (Frontiers in Toxicology, 2022)
Introduction: Many people living with HIV/AIDS (PLHIV) in Uganda widely use herbal medicines. However, the toxicity and safety of the medicinal plants used have not been investigated, posing a potential threat to the health of patients. The purpose of this study was to determine the cytotoxicity of several commonly used medicinal plant species. Material and methods: The cytotoxicity of the plant extracts was determined with the AlamarBlue cell viability assay using the human glioblastoma cell line U87.CD4.CXCR4. The cells were treated with varying concentrations of extracts of Warburgia ugandensis, Erythrina abyssinica, Cryptolepsis sanguinolenta, Albizia coriaria, Psorospermum febrifugium, Gymnosporia senegalensis, Zanthoxylum chalybeum, Securidaca longipendunculata, Vachellia hockii, Gardenia ternifolia Subsp. jovis-tonantis and Bridelia micrantha reconstituted with ethanol and dimethyl sulfoxide (DMSO). The half maximal cytotoxic concentration (CC50) of the plant extracts were calculated using exponential curve fits. Results: Both the ethanol and DMSO-reconstituted extracts of W. ugandensis and A. coriria were highly cytotoxic (CC50 = 7.6 and 1.5 µg/ml and 6.4 and < 4 µg/ml) respectively. The cytotoxicity of W. ugandensis and A. coriaria correlated well with the indigenous traditional knowledge of the toxic side effects experienced with the incorrect use of the plants. Most of the plant extracts (15/22) were moderately cytotoxic (CC50 = 21-200 µg/ml). The ethanol extracts were generally less toxic than the extracts reconstituted with DMSO. Conclusion: The DMSO-reconstituted extracts of the plant species tested were generally more cytotoxic to the cells than the ethanol extracts.